2010
DOI: 10.17221/73/2009-pse
|View full text |Cite
|
Sign up to set email alerts
|

Plant and row spacing effects on soil water and yield of rainfed summer soybean in the northern China

Abstract: Productivity and water resource-use efficiency are crucial issues in sustainable agriculture, especially in high-demand water resource crops such as soybean [Glycine max (L.) Merr.]. The aims of this research were to compare planting pattern in soybean, evaluating soil moisture content (SMC), yield and water use efficiency (WUE). A 2-year field experiment (2006–2007) was carried out in the north of China. The summer soybean (cv. Ludou 4) experiment consisted of 5 planting patterns under the same plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
1
9
1
Order By: Relevance
“…They reported that plants produced at higher densities were taller, lodged more, were more sparsely branched, set fewer pods and seed than those plants at lower densities. Similarly, [160] observed that plant and row spacing improve WUE and yield components in soybean. Agajie et al [161] studied the effect of spacing on yield components and yield of chickpea.…”
Section: Management Strategiesmentioning
confidence: 93%
“…They reported that plants produced at higher densities were taller, lodged more, were more sparsely branched, set fewer pods and seed than those plants at lower densities. Similarly, [160] observed that plant and row spacing improve WUE and yield components in soybean. Agajie et al [161] studied the effect of spacing on yield components and yield of chickpea.…”
Section: Management Strategiesmentioning
confidence: 93%
“…The plants compete with each other for light, water and nutrients. Gaseous exchange between the crop and atmosphere depends on the canopy architecture of plants (Zhou et al, 2010).…”
Section: Harvest Index and Biomass Weightmentioning
confidence: 99%
“…For such layer widths and at L-band, no azimuthal brightness temperature variations are expected. However, two points need to be taken into account: Firstly, 18-19 cm row widths are not uncommon for soybean stands [47][48][49] and have been reported in previous studies for corn stands (although uncommon) [49]. Under extreme conditions such as highly localized irrigation, such row spacings might result in soil moisture patterns of ∼ 9-10 cm layer widths.…”
Section: Permittivity Patterns In Real-world Scenariosmentioning
confidence: 94%